Promosi Penjualan Thrift Shop di Media Sosial Instagram - Dindra Harianto; Aning Sofyan (Bandung Conference Series: Communication Management, 2022)
Abstract. In this era of globalization, the fashion business has experienced very significant growth, one of which is in Bandung. TILAS Berkelas is one of the businesses in the fashion sector in Majalaya, Bandung Regency, which has its own uniqueness in terms of presenting content and in terms of sales. The purpose of this study was to find out how to present thriftshop advertisements on Instagram, promote sales of preloved products, barriers to promotion of preloved products and efforts to overcome them, as well as the reasons for choosing Instagram Feeds and Insta Story features to be the mainstay. So this research is expected to gain more knowledge for other researchers regarding the promotion of Preloved Products through Instagram, and it is hoped that there will be more developments for TILAS Berkelas regarding the presentation of advertisements and content as product promotions. This study uses a qualitative research method with a case study approach. Data collection techniques used are observation, interviews, documentation, and literature study. The subjects of this research are the owners, Instagram admins and TILAS Berkelas consumers.The result of this research is that @tilas.berkelas uses the feeds and Instagram Story features to present their sales promotion advertisements. Sales promotions carried out by @tilas.berkelas are price discounts, give aways and special steal deals. Their sales promotion aims to introduce and attract many consumers to buy the products they sell. The obstacle that is often experienced in conducting sales promotions is the Instagram algorithm which changes frequently. With these obstacles, @tilas.berkelas also often uses the personal accounts of friends of shop owners and employees to promote their brands. The features that are often used by @tilas.berkelas are feeds and Instagram Stories to present promotional content and product photos.Abstrak. Di era globalisasi ini bisnis fashion mengalami pertumbuhan yang sangat signifikan, salah satunya di Bandung. TILAS Berkelas merupakan salah satu usaha dibidang fashion di Majalaya Kabupaten Bandung, yang memiliki keunikan tersendiri dari segi menyajian konten dan dari segi penjualannya. Tujuan penelitian ini untuk mengetahui bagaimana penyajian iklan thriftshop di instagram, promosi penjualan produk preloved, hambatan promosi produk preloved dan upaya mengatasinya, serta alasan memilih fitur Instagram Feeds dan Insta Story menjadi andalan. Maka penelitian ini diharapkan dapat memberikan pengetahuan yang lebih bagi peneliti lain mengenai Promosi Produk Preloved melalui Instagram, serta diharapkan adanya perkembangan lebih bagi TILAS Berkelas mengenai penyajian iklan dan konten sebagai kegiatan promosi produknya. Penelitian ini menggunakan metode penelitian kualitatif dengan pedekatan studi kasus. Teknik pengumpulan data yang digunakan adalah, observasi, wawancara, dokumentasi, dan studi kepustakaan. Subjek penelitian ini yaitu pemilik, admin instagram dan Konsumen TILAS Berkelas. Hasil dari penelitian ini adalah akun @tilas.berkelas menggunakan fitur feeds dan Instagram Story untuk menyajikan iklan promosi penjualan mereka. Promosi penjualan yang dilakukan oleh akun @tilas.berkelas adalah memberikan potongan harga, give away dan special steal deal. Promosi penjualan yang mereka lakukan bertujuan untuk mengenalkan dan menarik banyak konsumen untuk membeli produk yang mereka jual. Hambatan yang sering dialami dalam melakukan promosi penjualan, yaitu alogoritma Instagram yang sering berubah. Dengan adanya hambatan tersebut, akun @tilas.berkelas juga sering memanfaatkan akun pribadi teman-teman dari pemilik toko dan pegawainya dalam mempromosikan brand mereka. Fitur yang sering dipakai oleh akun @tilas.berkelas adalah feed dan Instagram Story untuk menyajikan konten-konten promosi dan foto produk.